2020
DOI: 10.1103/physrevd.102.034031
|View full text |Cite
|
Sign up to set email alerts
|

Electrically charged strange stars with an interacting quark matter equation of state

Abstract: The properties of electrically charged strange quark stars predicted by an interacting quark matter equation of state (EoS) based on cold and dense perturbative quantum chromodynamics (pQCD) are investigated. The stability of strange stars is analyzed considering different models for the electric charge distribution inside the star as well as for distinct values for the total electric charge. A comparison with the predictions derived using the MIT bag model is also presented. We show that the presence of a net… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
(75 reference statements)
3
21
0
Order By: Relevance
“…In particular, in Ref. [30], two of the authors have studied the properties of charged strange stars considering an EoS based on perturbative QCD and demonstrated that the presence of an electric charge distribution implies that the maximum mass is larger in comparison to the neutral counterpart, in agreement with the results obtained in Ref. [32] using a simplified approach (see also Refs.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…In particular, in Ref. [30], two of the authors have studied the properties of charged strange stars considering an EoS based on perturbative QCD and demonstrated that the presence of an electric charge distribution implies that the maximum mass is larger in comparison to the neutral counterpart, in agreement with the results obtained in Ref. [32] using a simplified approach (see also Refs.…”
Section: Introductionsupporting
confidence: 77%
“…In this section, we will present a brief review of the theoretical framework necessary to investigate electrically charged compact stars (see Refs. [30][31][32]34,35] for extensive details). Initially, we will present the electrically-charged structure equations and the model for the electric charge distribution used in this work.…”
Section: Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the possibility for GW190814's secondary as a neutron star can be accomplished by: (1) choosing/constructing stiff EOSs having a maximum mass larger than 2.5 M [76,[141][142][143][144][145][146][147][148][149][150]; (2) considering the effects of fast rotations, which can increase the maximum mass by about 20% when a star rotates at the Kepler frequency (the maximum frequency at which the gravitational attraction is still sufficient to keep matter bound to the pulsar surface) [42,43,139,140,145,[151][152][153][154][155][156][157] ; (3) considering other effects/models that can modify the maximum mass of a neutron star, such as the magnetic field [147], twin star [158], two families of compact stars [142], finite temperature [153], antikaon condensation [159], net electric charge [144], etc.…”
Section: Is Gw190814's Secondary a Superfast And Supermassive Neutron Star Or Something Else?mentioning
confidence: 99%